Apolipoprotein E Deficiency Aggravates Neuronal Injury by Enhancing Neuroinflammation via the JNK/c-Jun Pathway in the Early Phase of Experimental Subarachnoid Hemorrhage in Mice. (26th December 2019) - Wu, Yue; Pang, Jinwei; Peng, Jianhua; Cao, Fang; Guo, Zongduo; Jiang, Li; Teng, Zhipeng; Huang, Zhijian; Cheng, Chongjie; Jiang, Yong; Sun, Xiaochuan
Abstract : Neuronal injury is the primary cause of poor outcome after subarachnoid hemorrhage (SAH). The apolipoprotein E (APOE) gene has been suggested to be involved in the prognosis of SAH patients. However, the role of APOE in neuronal injury after SAH has not been well studied. In this study, SAH was induced in APOE-knockout (APOE -/- ) and wild-type (WT) mice to investigate the impact of APOE deficiency on neuronal injury in the early phase of SAH. The experiments of this study were performed in murine SAH models in vivo and primary cultured microglia and neurons in vitro. The SAH model was induced by endovascular perforation in APOE -/- and APOE WT mice. The mortality rate, weight loss, and neurological deficits were recorded within 72 h after SAH. The neuronal injury was assessed by detecting the neuronal apoptosis and axonal injury. The activation of microglia was assessed by immunofluorescent staining of Iba-1, and clodronate liposomes were used for inhibiting microglial activation. The expression of JNK/c-Jun was evaluated by immunofluorescent staining or western blotting. The expression of TNF- α, IL-1 β, and IL-6 was evaluated by ELISA. Primary cultured microglia were treated with hemoglobin (Hb) in vitro for simulating the pathological process of SAH. SP600125, a JNK inhibitor, was used for evaluating the role of JNK in neuroinflammation. Nitrite production was detected for microglial activation, and flow cytometry was performed to detect apoptosis in vitro. The results suggested that SAH induced early neuronal injury and neurological deficits in mice. APOE deficiency resulted in more severe neurological deficits after SAH in mice. The neurological deficits were associated with exacerbation of neuronal injury, including neuronal apoptosis and axonal injury. Moreover, APOE deficiency enhanced microglial activation and related inflammatory injury on neurons. Inhibition of microglia attenuated neuronal injury in mice, whereas inhibition of JNK inhibited microglia-mediated inflammatory response in vitro. Taken together, JNK/c-Jun was involved in the enhancement of microglia-mediated inflammatory injury in APOE -/- mice. APOE deficiency aggravates neuronal injury which may account for the poor neurological outcomes of APOE -/- mice. The possible protective role of APOE against EBI via the modulation of inflammatory response indicates its potential treatment for SAH.